STUDI EFEKTIFITAS BUKU SAKU TERHADAP SKOR PENGETAHUAN PENYAKIT MENULAR SEKSUAL PADA SISWA SMA NEGERI BANYUMAS - Vitria Sari, Noor Linda; Suryandari, Artathi Eka; Santjaka, Aris (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Teenagers are one of high infectious sexual disease (ISD) risk cluster. It needs an effort to prevent Infectious sexual disease case in teenagers by promoting good health media such a pocket-book. The aim of the research is to prove the influence of ISD pocket-book and the students’ knowledge of infectious sexual disease scoring development in SMA Negeri Banyumas.This research belongs to pre-experimental research that uses the one group pretest and post test design. The population of the research is the 10th year students of SMA Negeri Banyumas which takes 72 students as the sample. The frequency distribution and Anova One Way are used in analyzing the data.The research result showed that average score of respondents’ ISD knowledge before pocket-book publication (pretest) is 67,54. It increases 20,2% from the pretest to 81,18 in seventh day after the publication (post test 1). After 14 days of book publication, respondents’ score increases 31,2% from pretest to 88,63%, or it increase 9,2% from post test 1. 3) There is signification showed by statistic result wherein p < α = 0,000<0,05. Advanced test shows significantly different scores among pre test score, post test 1 and post test 2. As the conclusion, pocket-book effectively increases students’ knowledge of infectious sexual disease scoring. As the recommendation, pocket-book can be used  to improve teenagers’ knowledge of  infectious sexual disease. Key Words : Students’ knowledge score pocket-book publication